Synthesis methodology and software implementation system evaluation harm to national security in protection of state secrets - Корченко, Олександр Григорович; Луцький, Максим Георгійович; Захарова, Марія В’ячеславівна; Дрейс, Юрій Олександрович (Ukrainian Information Security Research Journal, 2013)
Attributing the information to the state secrets held by state expert on secrets by setting, justification and determination of possible damage to national security if such disclosure for a decision on their degree of secrecy. Existing means of calculating such damage is overwhelmingly based on a conditional (scoring) assess its predicted value. The paper presents the methodology for the synthesis of systems analysis and estimation of possible damage to national security that allows model-based integrated presentation of damage parameters obtained by existing analysis tools in the protection of state secrets, to assess the damage as in conventional (ball) units and in value (monetary) value of loss. Founded she developed method: analysis and assessment of damage to national security in the protection of state secrets, assessing the importance of information on certain areas of state secrets, determine the level of competence of the expert committee members at state expert on secrets. In addition, the methodology enables to display the results in both qualitative and quantitative form, for example, using linguistic variables that are often used to describe complex systems. Software implementation of the system with an integrated database of existing tools allows an analysis and estimate of the possible damage to national security with additional automated reporting its results.